The Role of Genetic Variation Near Interferon-kappa in Systemic Lupus Erythematosus. (10th June 2010) - Harley, Isaac T. W.; Niewold, Timothy B.; Stormont, Rebecca M.; Kaufman, Kenneth M.; Glenn, Stuart B.; Franek, Beverly S.; Kelly, Jennifer A.; Kilpatrick, Jeffrey R.; Hutchings, David; Divers, Jasmin; Bruner, Gail R.; Edberg, Jeffrey C.; et al.
Abstract : Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by increased type I interferons (IFNs) and multiorgan inflammation frequently targeting the skin. IFN-kappa is a type I IFN expressed in skin. A pooled genome-wide scan implicated the IFNK locus in SLE susceptibility. We studied IFNK single nucleotide polymorphisms (SNPs) in 3982 SLE cases and 4275 controls, composed of European (EA), African-American (AA), and Asian ancestry. rs12553951C was associated with SLE in EA males (odds ratio = 1.93, P = 2.5 × 10 − 4 ), but not females. Suggestive associations with skin phenotypes in EA and AA females were found, and these were also sex-specific. IFNK SNPs were associated with increased serum type I IFN in EA and AA SLE patients. Our data suggest a sex-dependent association between IFNK SNPs and SLE and skin phenotypes. The serum IFN association suggests that IFNK variants could influence type I IFN producing plasmacytoid dendritic cells in affected skin.